Egg, M. 2021. Aspectual Composition: “Drinking (A Glass of) Milk”. D. Gutzmann; L. Matthewson; C. Meier; H. Rullman & T. E. Zimmermann (Eds.). The Wiley Blackwell Companion to Semantics (1rst ed.). Vol. 1. Hoboken: Wiley, pp. 91-120. - Cantante, Inês (elingUP: Revista Eletrónica de Linguística dos Estudantes da Universidade do Porto, 2023)
.